Thermal Environmental Treatments for residential buildigs In the oil fields - Younis Mahmood Saleem; Hadeer Shallal Aljaber (Iraqi Journal of Architecture and Planning, 2018)
The industry growth and  development was one of the reasons for the emergence of cities, the oil industry has been affected in the establishment of these cities in the environmental aspects, Oil fields are considered heavy industry areas.The research aims: Identification of environmental treatments which make the building efficient thermally and therefore to reduce the impact of climatic conditions and pollution In urban complexes inside the oil fields .The research concluded a set of conclusions which have been associated two sides: First side has been associated in the theoretical framework, the flipside link to the results of the practical application. The research found the environmental treatments of urban complexes Inside the local oil fields,  Impact in improving the residential environment inside that complexes commensurate with distance from the sources of environmental pollution and improve the efficiency of the thermal performance of residential units.